Hypothyroidism causing paralytic ileus and acute kidney injury - case report - Rodrigo, C.; Gamakaranage, C.S.; Epa, D.S.; Gnanathasan, A.; Rajapakse, S. (My University, 2011)
We present a patient with severe hypothyroidism complicated by paralytic ileus and acute kidney injury. A 65 year old male patient, diagnosed with hypothyroidism one year ago was transferred to our unit in a state of drowsiness and confusion. He was severely hypothyroid and had paralytic ileus and impaired renal function at the time of transfer. Hypokalaemia was present, and was likely to have contributed to the paralytic ileus and this together with dehydration was likely to have contributed to renal injury. Nonetheless, hypothyroidism is very likely to have been the principal precipitant of both these complications, and both paralytic ileus and acute kidney injury improved with thyroxine replacement. Unfortunately, the patient died unexpectedly eight days after admission to the unit.Hypothyroidism may induce de novo acute kidney injury or it may exacerbate ongoing chronic kidney disease. This rare complication is assumed to be due to the hypodynamic circulatory state created by thyroid hormone deficiency. Paralytic ileus is an even rarer fatal manifestation of hypothyroidism and is thought to be due to an autonomic neuropathy affecting the intestines that is reversible with thyroxine replacement. To our knowledge, both these complications have not been observed in a single patient so far.It is important that clinicians are aware of these rare manifestations of hypothyroidism as in most occasions, thyroxine deficiency may be missed, and treatment can reverse the complications.